Teachers' Pedagogical Understanding in the Implementation of Independent Curriculum in the Context of Deep Learning - Arina, Ida; Isyanto, Puji (LPPM Institut Pendidikan Nusantara Global, 2025)
The implementation of the Independent Curriculum is a government effort to improve the quality of education in Indonesia. Developing teachers' pedagogical understanding is very important to improve the quality of learning in the classroom. One approach that can be used is Deep Learning, which focuses on developing critical thinking and problem-solving skills to improve the quality of learning. This article discusses the importance of teachers' pedagogical understanding in the implementation of the Independent Curriculum with the Deep Learning approach, as well as the challenges and opportunities faced by teachers. This study uses a descriptive qualitative method with a case study to describe teachers' teaching competence in independent learning. Researchers collected data through interviews and observations, and analyzed information obtained from participants. The results of the analysis are presented in a descriptive form that is in accordance with the topic of discussion. This study involved interviews with teachers and principals at SDN Kota Karawang and was supported by library research. Based on the analysis of pedagogical understanding in the implementation of the Independent Curriculum in the context of Deep Learning, it can be concluded that a deep pedagogical understanding of teachers is very important to improve the quality of education. Teachers who have a good pedagogical understanding can develop a curriculum that is in accordance with the needs of students and the community, and can improve the quality of teaching in the classroom.